2020
DOI: 10.3390/foods9050636
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Emulsifying Properties of Food Protein Hydrolysates for the Production of Fish Oil-in-Water Emulsions

Abstract: The incorporation of lipid ingredients into food matrices presents a main drawback—their susceptibility to oxidation—which is associated with the loss of nutritional properties and the generation of undesirable flavors and odors. Oil-in-water emulsions are able to stabilize and protect lipid compounds from oxidation. Driven by consumers’ demand, the search for natural emulsifiers, such as proteins, is gaining much interest in food industries. This paper evaluates the in vitro emulsifying properties of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…The observed levels for EAI and ESI are in good agreement with previous studies of FPHs, where EAI is generally reported to be in the range 25-270 m2/g and ESI in the range 22-48 min [8]. In comparison, hydrolysates from soy and whey protein have been reported to possess EAI in the range 2-12 m2/g and ESI in the range 10-40 min [47]. Consequently, FPHs possess much higher emulsifying activity without any cost in emulsion stability.…”
Section: Bulk Emulsifying Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…The observed levels for EAI and ESI are in good agreement with previous studies of FPHs, where EAI is generally reported to be in the range 25-270 m2/g and ESI in the range 22-48 min [8]. In comparison, hydrolysates from soy and whey protein have been reported to possess EAI in the range 2-12 m2/g and ESI in the range 10-40 min [47]. Consequently, FPHs possess much higher emulsifying activity without any cost in emulsion stability.…”
Section: Bulk Emulsifying Propertiessupporting
confidence: 90%
“…This covers inclusion of aromatic AAs such as Tyr, Trp and Phe [47,68,69], hydrophobic AAs including Val, Leu and Ala [47,[68][69][70][71] sulphur-containing AAs, i.e. Met and Cys [47,68,69], acidic AAs, i.e. Glu and Asp [70,72], alkaline AAs, i.e.…”
Section: Bulk Antioxdiative Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…New strategies have also been employed to generate novel Pickering emulsions. Okara dietary fiber particulate obtained via Maillard reaction and protein Hydrolysates showed great efficiency in building the split-new emulsion systems [35,36]. Moreover, the HIPEs stabilized by these particles have also been declared to be a promising template for the constructing of biocompatible scaffold for 3D cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…This approach requires emulsifiers with good emulsifying properties for preparing emulsions with high physical and oxidative stability. Padial-Dominguez and co-workers optimized the enzymatic hydrolysis conditions used for the preparation of hydrolysates of whey protein and soy protein with optimal emulsifying properties [ 3 ]. They also investigated the physical and oxidative stability of fish oil-in-water emulsions prepared with soy protein hydrolysates.…”
mentioning
confidence: 99%